1992
DOI: 10.1128/aem.58.12.3826-3829.1992
|View full text |Cite
|
Sign up to set email alerts
|

The Entner-Doudoroff pathway in Escherichia coli is induced for oxidative glucose metabolism via pyrroloquinoline quinone-dependent glucose dehydrogenase

Abstract: The Entner-Doudoroff pathway was shown to be induced for oxidative glucose metabolism when Escherichia coli was provided with the periplasmic glucose dehydrogenase cofactor pyrroloquinoline quinone (PQQ). Induction of the Entner-Doudoroff pathway by glucose plus PQQ was established both genetically and biochemically and was shown to occur in glucose transport mutants, as well as in wild-type E. coli. These data complete the body of evidence that proves the existence of a pathway for oxidative glucose metabolis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…All these indicated existence of differential regulation of edd and eda in V. cholerae which are in bi-directional operon (19). Observed differential regulation of the edd and eda transcripts have also been reported earlier for other organisms (36)(37)(38)(39). It has also been established earlier that V. cholerae preferentially utilizes glucose through EMP pathway in M9-glucose medium (18).…”
Section: Accepted Manuscriptsupporting
confidence: 78%
“…All these indicated existence of differential regulation of edd and eda in V. cholerae which are in bi-directional operon (19). Observed differential regulation of the edd and eda transcripts have also been reported earlier for other organisms (36)(37)(38)(39). It has also been established earlier that V. cholerae preferentially utilizes glucose through EMP pathway in M9-glucose medium (18).…”
Section: Accepted Manuscriptsupporting
confidence: 78%
“…Results showed that under aerobic, but not anaerobic, conditions functional glucose dehydrogenase allowed growth on glucose of double mutants blocked at phosphoglucose isomerase and glucose-6-phosphate dehydrogenase (1). Subsequent experiments provided direct evidence that the ED pathway is turned on by oxidation of glucose to gluconate in the periplasm (27). The oxidative glucose pathway might be important for survival of E. coli in aerobic, aquatic environments.…”
Section: Oxidative Glucose Metabolismmentioning
confidence: 99%
“…This ED cycle was observed on glucose in Azotobacter vinelandii and other Pseudomonas species synthesizing alginate, a polysaccharide metabolically derived from fructose‐6‐phosphate (F6P). Two complementary explanations have been proposed for the operation of the ED cycle: (i) a low phosphoglucoisomerase (PGI) activity [6,7] that is further inhibited by intermediates of glucose catabolism [1] and (ii) the occurrence of the periplasmic oxidation of glucose into gluconate which feeds the catabolic pathways at the level of 6‐phosphogluconate and acts as an inducer of ED enzymes [8,9] but does not enable hexose‐phosphate formation (gluconate bypass) because of the irreversibility of the glucose‐6‐phosphate (G6P) dehydrogenase reaction. Both features generated a situation where F6P could not be obtained directly from the exogenous glucose and the anabolic demands in F6P were fulfilled by the operation of the cyclic ED pathway [5], that acted as an alternative route for the conversion of G6P into F6P.…”
Section: Introductionmentioning
confidence: 99%